2018
DOI: 10.1080/14767058.2018.1449207
|View full text |Cite
|
Sign up to set email alerts
|

Fetus-in-fetu: two case reports

Abstract: The objective of our study is to describe the sonographic findings of an extremely rare pathology. We therefore present two case reports of prenatal diagnosis of fetus-in-fetu (FIF) with a review of the literature. FIF is a benign disorder, unlike the teratoma with which often enter into the differential diagnosis, localized in most cases in the retroperitoneal space. Prenatal diagnosis is based mainly on ultrasound and radiological characteristics. The treatment of choice is surgical excision. The importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 29 publications
2
16
0
1
Order By: Relevance
“…With the advance of acoustics technology, ultrasound could be used to detect such malformation in utero. Most of cases with FIF were detected in 2nd and 3rd trimester [4]. Our case was demonstrated at 16 weeks’ gestation, the most early gestation age reported so far.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…With the advance of acoustics technology, ultrasound could be used to detect such malformation in utero. Most of cases with FIF were detected in 2nd and 3rd trimester [4]. Our case was demonstrated at 16 weeks’ gestation, the most early gestation age reported so far.…”
Section: Discussionmentioning
confidence: 62%
“…Skin, intestinal, bones, cartilage, lung, and adrenal tissue were also often present. A review [4] of reported 32 prenatal cases of FIF concluded that 90% of cases had a vertebral column, 90% had recognize bony extremity or rudimentary limb, 60% had central nervous tissue, 26% had gastrointestinal tissue, and 20% had respiratory tissue. All of reported FIF were acardiac except one case which found rudimentary heart structure by postnatal ultrasound [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 It is usually not a malignant condition, but it can cause abdominal distension, problems during feeding, vomiting, jaundice, renal and respiratory disorders. 12 In this case, the patient presented a stable clinical picture, without physical alterations, absence of jaundice and satisfactory suction.…”
Section: Discussionmentioning
confidence: 66%